Colloidal Synthesis of Chromium Phosphide Assisted by Partial Oxidation and Its Electrocatalytic Activity in Oxygen Reduction Reaction - Woo, Chaeheon; Chae, Sudong; Kim, Tae Yeong; Jeon, Jiho; Dong, Xue; Asghar, Ghulam; Choi, Kyung Hwan; Oh, Seungbae; Ahn, Jungyoon; Zhang, Xiaojie; Yu, Hak Ki; Choi, Jae Young (Crystal Growth and Design, 2022)
Due to their outstanding performance in valuable electrochemical reactions, transition-metal phosphides (TMPs) have emerged as promising electrocatalysts. The low boiling point of the intermediate reactants was a significant obstacle in synthesizing various TMPs. The present work describes a highly reproducible and cost-effective method for synthesizing chromium phosphide (CrP) nanoparticles using a volatile transition-metal precursor. We successfully synthesized crystallinity-controllable CrP nanoparticles using a partially oxidized chromium compound. The obtained CrP nanoparticles have demonstrated highly selective and stable catalytic performance in the oxygen reduction reaction, with an electron-transfer number of 3.93 in a 0.1 M KOH solution.
Keywords: Colloidal synthesis; Cost-effective methods; Electrocatalytic activity; Electrochemical reactions; Metal precursor; Oxygen reduction reaction; Partial oxidations; Performance; Synthesised; Transition metal phosphide